Efficient leadership: a systemic model of prophetic thinking = Kepimpinan yang berkesan: model sistemik dari pemikiran Nabi - Badi, Jamal Ahmed Bashier (IIUM Press, International Islamic University Malaysia, 2017)
Efficient leadership and systemic thinking are issues over which modern scholars have paid special attention to. Many books based on thorough investigation into these two issues have been written down. These works originally represent speculations from theoretical angle. Practical evidences derived from the history are almost missing from these efforts. History serves as a source of lessons related to all dimensions of human life, including leadership and systemic thinking. The Last Prophet peace be upon him was the most effective leader the history ever witnessed. Reading his life-history, particularly the events linked with his 23year Islamic mission can lead to the most striking features of the most effective leadership traits—complete trust in Allah the Ultimate Source of everything, honesty towards Allah as well as fellow human beings, patience in diversity, forbearance in all situations, humbleness and humility, owning responsibility for all untoward incidents, decisiveness in difficult matters, and firmness over the stand taken. The Last Prophet’s peace be upon him life has been studied and are still being studied from various angles, social, political, and spiritual, but one may hardly lay one’s hands on a work on the biography of the Prophet peace be upon him that has been written from the angle of efficient leadership and systemic thinking. This short paper represents a humble effort to read the Last Prophet’s peace be upon him history with a view to regenerating traits of the most efficient leadership.